PENGARUH HARGA, KUALITAS PRODUK, LIFESTYLE, DAN ISLAMIC BRANDING TERHADAP KEPUTUSAN PEMBELIAN PRODUK RABBANI(Studi pada Konsumen Toko Purnama Moslem Store Muara Sabak Barat) - Ambar wati, Wilis; Wati, Wilis Ambar; Rafidah, Rafidah; Siregar, Fitri Ana (Manajemen Keuangan Syariah, 2025)
This study aims to determine the effect of price, product quality, lifestyle, and Islamic branding on purchasing decisions both simultaneously and partially, and to determine the most dominant variable. The subjects of the study were all consumers of the Purnama Moslem Store who had purchased Rabbani products, totaling 96 respondents. Considering the unknown population size, a purposive sampling method was used in determining the sample in this study using the Lemeshow formula technique for sampling. Data collection was carried out through questionnaires and data analysis using multiple linear regression analysis. The results of this study indicate that simultaneously price, product quality, lifestyle, and Islamic branding have a significant effect on purchasing decisions. Partially, price has a positive and significant effect on purchasing decisions, product quality has a negative and significant effect on purchasing decisions, lifestyle has a positive and significant effect on purchasing decisions, and Islamic branding has a positive and significant effect on purchasing decisions. Among these variables, Islamic branding is the most dominant factor influencing purchasing decisions.